2022
DOI: 10.1101/2022.04.25.489366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ancient dental calculus preserves signatures of biofilm succession and inter-individual variation independent of dental pathology

Abstract: Dental calculus preserves oral microbes, enabling comparative studies of the oral microbiome and health through time. However, small sample sizes and limited dental health metadata have hindered health-focused investigations to date. Here we investigate the relationship between tobacco pipe smoking and dental calculus microbiomes. Dental calculus from 75 individuals from the 19th century Middenbeemster skeletal collection (Netherlands) were analyzed by metagenomics. Demographic and dental health parameters wer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 102 publications
1
4
0
Order By: Relevance
“…However, the extent to which loss of AT-rich fragments affects species profiles, perhaps skewing older samples to have higher proportions of high-GC taxa, has not yet been extensively explored. We found that the species with the strongest PC1 loadings (Supplemental Table S3) suggested a taxonomic gradient relating to oxygen tolerance, such as that previously described in calculus samples from the archaeological site of Middenbeemster in the Netherlands 15 , but there was no clear association with GC content.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…However, the extent to which loss of AT-rich fragments affects species profiles, perhaps skewing older samples to have higher proportions of high-GC taxa, has not yet been extensively explored. We found that the species with the strongest PC1 loadings (Supplemental Table S3) suggested a taxonomic gradient relating to oxygen tolerance, such as that previously described in calculus samples from the archaeological site of Middenbeemster in the Netherlands 15 , but there was no clear association with GC content.…”
Section: Resultssupporting
confidence: 54%
“…When controlling for the lab in which samples were processed, island (R 2 = 0.2045, F = 1.650, p = 0.035) and average GC content (R 2 = 0.0761, F = 7.372, p = 0.01) were still significant drivers of the sample community composition. The average GC content of calculus is known to increase with sample age 11,14,15 through the taphonomic loss of AT-rich DNA fragments, and most islands are represented by samples from a single time period, therefore tying island and age/GC content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations